2021
DOI: 10.1002/ehf2.13696
|View full text |Cite
|
Sign up to set email alerts
|

Dose of furosemide before admission predicts diuretic efficiency and long‐term prognosis in acute heart failure

Abstract: Aims The outpatient diuretic dose is a marker of diuretic resistance and prognosis in chronic heart failure (HF). Still, the impact of the preadmission dose on diuretic efficiency (DE) and prognosis in acute HF is not fully known. Methods and results We conducted an observational and prospective study. All patients admitted for acute HF treated with intravenous diuretic and at least one criterion of congestion on admission were evaluated. Decongestion [physical examination, hemoconcentration, N‐terminal pro‐br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Forth, the patients who participated in the trial had a history of chronic HF and required moderate-to-high doses of loop diuretics before admission (which is the case for 20-30% of patients with chronic HF who are admitted due to decompensation). 24,25 Our findings may not be applicable to patients with newly diagnosed HF or those with more modest diuretic requirements. Finally, in the followup visits, neither renal function nor electrolytes were monitored, so we cannot guarantee that the worsening of renal function is transient and associated with a good diuretic response.…”
Section: Discussionmentioning
confidence: 81%
“…Forth, the patients who participated in the trial had a history of chronic HF and required moderate-to-high doses of loop diuretics before admission (which is the case for 20-30% of patients with chronic HF who are admitted due to decompensation). 24,25 Our findings may not be applicable to patients with newly diagnosed HF or those with more modest diuretic requirements. Finally, in the followup visits, neither renal function nor electrolytes were monitored, so we cannot guarantee that the worsening of renal function is transient and associated with a good diuretic response.…”
Section: Discussionmentioning
confidence: 81%
“…A study conducted by Bermejo, Z.B, et al (2022) also found that in patients with AHF, the presence of a history of pre-admission diuretic use > 80 mg/day was associated with a worse disease prognosis (log rank < 0.001). In patients with AHF, pre-admission furosemide dose was independently associated with both mortality and rehospitalization due to HF [33].…”
Section: Discussionmentioning
confidence: 97%
“…The water-regulating effects of Goreisan have the potential to reduce the reliance on conventional loop diuretics and aid in preserving renal function, which were associated with poor prognosis in HFpEF patients [ 9 ]. Moreover, Goreisan has pleiotropic effects in cardiomyocytes where aquaporin 1, 4, and 7 are expressed, as it has been shown to suppress the upregulation of aquaporin 4 gene expression [ 5 , 10 ].…”
Section: Discussionmentioning
confidence: 99%